KAJIAN SINTAKSIS DAN MORFOLOGIS TERHADAP TEKS PROKLAMASI: STRUKTUR DAN MAKNANYA - Yemima, Queen; Hutagalung, Nurhabibah; Sihombing, Melica; Gultom, Theresia Marlina Yopita; Jakaria, Jakaria (Universitas Sultan Ageng Tirtayasa, 2025)
This research analyzes the syntactic and morphological aspects of the Indonesian Proclamation Text to understand its structure and meaning. Syntax focuses on sentence structure and the relationships between sentence elements, while morphology studies word formation and how words change to convey meaning. The study uses a qualitative descriptive method to examine the linguistic patterns in the proclamation text, comparing them with other formal texts such as academic and news texts. The syntactic analysis reveals that the proclamation text follows a clear and structured pattern, ensuring its message is conveyed effectively. The first sentence employs a subject-verb-object (SVO) structure, making the declaration direct and authoritative. Meanwhile, the second sentence uses a passive construction, emphasizing the collective responsibility in the transition of power. Morphological analysis shows the use of affixation, such as prefixes and suffixes, which strengthen the formal and official nature of the text. The findings highlight the effectiveness of the text in delivering a strong and unambiguous message, By understanding the linguistic structures within the proclamation, this study provides insights into the role of language in historical and national identity. The research underscores the importance of proper syntactic and morphological structures in official documents to ensure clarity and impact.